Pengaruh Akuntabilitas dan Transparansi Terhadap Pengelolaan Keuangan Sekolah Menengah Atas (SMA) Negeri Se-Kota Bandung - Anita Syafariah (Jurnal Ekonomi Manajemen Perbankan, 2020)
Accountability and transparency are an inseparable unit in financial management. Accountability is defined as the ability to show reports or records that can be accounted for. While transparency is openness regarding financial management information that can be accessed by parents, the community and the government. In preparing the School Expenditure Budget Plan (RAPBS) the process of planning, organizing, directing, coordinating, reporting / accountability, and monitoring both internal and external to the school of financial managers and implementing activities is an effort in implementing accountable financial management and transparent. This research was conducted at Bandung City Public High Schools by involving 216 respondents from 540 people. The research method used is descriptive method with sampling technique that is cluster sampling method with multiple linear regression data analysis assisted by SPSS Ver program. 16. Data processing is done through transformation of data from ordinal to intervals and the test data used are the normality test, linearity test, validity test, reliability test, correlation analysis, multiple regression analysis, after research has shown that accountability and transparency affect the management of school finances and has a significant degree both partially and simultaneously.